Laevifins A–G, clerodane diterpenoids from the Bark of Croton oblongus Burm.f. - Aziz, Ahmad Nazif; Ismail, Nor Hadiani; Halim, Siti Nadiah Abdul; Looi, Chung Yeng; Anouar, El Hassane; Langat, Moses K.; Mulholland, Dulcie; Awang, Khalijah (Elsevier, 2018)
A phytochemical investigation of the stem barks of the Malaysian Croton oblongus Burm.f. (Syn. Croton laevifolius Blume) (Euphorbiaceae) yielded seven previously undescribed ent-neo-clerodane diterpenoids, laevifins A - G and the known crovatin (3). Structures were established by a combination of spectroscopic methods including HRESIMS, NMR spectroscopy and X-ray crystallography. The absolute configuration of crovatin and laevifins A-G was established by comparison of experimental ECD and theoretical TDDFT ECD calculated spectra. This is the first report on the occurrence of the sesquiterpenoid cryptomeridiol in a Croton species. In vitro cytotoxicity assays on laevifins A, B and G showed moderate activities against the MCF-7 cancer cell line (IC50 102, 115 and 106 μM, respectively) while β-amyrin and acetyl aleuritolic acid showed good anti-inflammatory activity on the LPS-induced NF-κB translocation inhibition in RAW 264.7 cells assay with IC50 values of 23.5 and 35.4 μg/mL, respectively.